Penentuan Kelompok Jaringan Logistik pada Wilayah Kepulauan menggunakan Fuzzy C-Means - Tri Kismanti, Sinta; Ard Maidah, Andi (Borneo Engineering : Jurnal Teknik Sipil, 2018)
Indonesia as the island nation with territorial waters is one of the modes of transportation. For this condition, most of activities are conducted in marine, such as logistics distribution. The movement of logistics distribution will result in a movement pattern of the logistic. Determination of the optimal pattern of logistics movement network can support the smooth distribution system. Determination of logistic network patterns is done by clustering using Fuzzy C-means, clustering aims to get island groups in adjacent locations. The clustering process using Fuzzy C-Means obtained that the number of clusters as many as 3 clusters showed better results compared to the number of clusters 4 and 5.